(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
Public expenditures undertaken by the government are the basic element in providing the public life requirements of individuals and thus achieving development goals in general. However، public expenditures in Iraq are characterized by the fact that a large portion of them goes as current expenditures، while a small portion of them is directed to investment in various economic sectors، including health. education and others. Therefore، the research concluded that there is a large deficit in Iraq between the great actual need for services and achieving the planned development requirements and the low actual reality، especially in the health sector. The research recommended that there should be special attention in this sector by the government to ensure Sustainable annual growth in providing and improving these services to all individuals in Iraq in order to achieve the sustainable development goals that the United Nations seeks to achieve until 2030.